2007
DOI: 10.3923/pjbs.2007.2500.2504
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Variant Transcripts of Waxy Gene in Non-glutinous Rice (O. sativa L.) With Different Amylose Content

Abstract: The identification of a number of cDNA sequences at the splice sites of Waxy (Wx) gene in rice endosperm point to the variation of gene expression associated with the G to T mutation at the 5' splice site of intron 1 and the alternative splicing produces variants transcripts by shortening. As consequence, variation of amylose content in this tissue. To determine whether the splicing type of Wx genes are also found in rice endosperm of Thai rice cultivars, cDNA of the gene have been isolated by using RT-PCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…As a consequence, the total amount of translatable Wx mRNA, and therefore the Wx protein and consequently amylose content, are reduced (Wang et al 1995;Cai et al 1998). Later studies further confirmed the importance of specific sequences in Wx intron 1 associated to the correct splicing of the pre-mRNA (Ayres et al 1997;Larkin and Park 1999;Isshiki et al 2000;Mikami et al 2000;Larkin and Park 2003;Bao et al 2006a;Prathepha 2007).…”
Section: Post-transcriptional Regulation Of Genes Involved In Grain Dmentioning
confidence: 85%
See 1 more Smart Citation
“…As a consequence, the total amount of translatable Wx mRNA, and therefore the Wx protein and consequently amylose content, are reduced (Wang et al 1995;Cai et al 1998). Later studies further confirmed the importance of specific sequences in Wx intron 1 associated to the correct splicing of the pre-mRNA (Ayres et al 1997;Larkin and Park 1999;Isshiki et al 2000;Mikami et al 2000;Larkin and Park 2003;Bao et al 2006a;Prathepha 2007).…”
Section: Post-transcriptional Regulation Of Genes Involved In Grain Dmentioning
confidence: 85%
“…The most well-studied molecular marker in the first intron of Wx gene is a single-nucleotide polymorphism (SNP), which is involved in the proper splicing of Wx mRNA. This SNP represents a naturally occurring G to T change resulting into two alleles named Wxa and Wxb which determine a significantly different amylose content resulting in the change of cooking properties and taste of rice (Wang et al 1995;Ayres et al 1997;Cai et al 1998;Mikami et al 2000;Larkin and Park 2003;Han et al 2004;Bao et al 2006a;Prathepha 2007;Chen et al 2008a,b). Besides this, also other SNPs were found in the Wx gene which are associated with variations in amylose content and viscosity characteristics (Sato et al 2002;Larkin and Park 2003;Chen et al 2008a,b;Tran et al 2011).…”
Section: Genetic Diversity In Starch Synthetase Genes Is Related To Tmentioning
confidence: 99%
“…EST sequencing has suggested that at least 20% of both Arabidopsis thaliana and rice genes are affected by AS (Buell et al 2006). In rice, traits and processes as diverse as the abiotic stress responses (Koo et al 2009;Matsukura et al 2010;Shi et al 2005), grain quality (Prathepha 2007), grain aroma Niu et al 2007) and photosynthetic rate (Isshiki et al 2000;To et al 1999) have all been shown to involve AS. The co-existence of both full-length and truncated transcripts is a welldocumented phenomenon, exactly as occurred for qFLW4/ NAL1 in cv.…”
Section: Discussionmentioning
confidence: 98%
“…RT-PCR with primers specific for unspliced variant of Wx transcript (Liu et al, 2009) confirmedthe absence of intron 1 containing 1.1 kb fragment in all of the selected Beruincultivars (Fig. 4B).A second set of RT-PCR primers previously described by Prathepha (2007) was used to re-confirm the absence of G/T SNP at intron1 splice donor site of Wx gene of these selected cultivars (Fig. 4C).…”
Section: 5wx Gene Expression In Selected Beruin Cultivars Without mentioning
confidence: 65%